2014
DOI: 10.1111/maec.12107
|View full text |Cite
|
Sign up to set email alerts
|

Macrobenthic composition of the southeast continental shelf of India

Abstract: Macrobenthic faunal composition was studied at six different depth ranges (30–50, 51–75, 76–100, 101–150, 151–175 and >176 m) in five transects (off Karaikkal, Parangipettai, Cuddalore‐SIPCOT, Cheyyur and Chennai) in the continental shelf of southeast coast of India. Eleven diverse taxa were found, comprising 113 species of polychaetes, 14 species of bivalves, 10 species of amphipods and ‘others’ (five tanaids, five crabs, four isopods, three echinoderms, two shrimps, two cnidarians, two fishes and one cephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…A few studies focused on the economically important bivalve species and associated conservation efforts (Rao, 1974; Kripa & Appukuttan, 2003). Various other studies reported overall diversity of organisms including bivalves from localities in the southern coast (Kurian, 1971; Khan et al , 2010; Kundu et al , 2010; Manokaran et al , 2015), east coast (Ansari et al , 1977; Mahapatro et al , 2011), and west coast (Parulekar, 1973; Parulekar & Dwivedi, 1974; Parulekar & Wagh, 1975; Jayaraj et al , 2007). Such studies conducted at a local scale, although common, may be limited in their utility in explaining larger patterns.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies focused on the economically important bivalve species and associated conservation efforts (Rao, 1974; Kripa & Appukuttan, 2003). Various other studies reported overall diversity of organisms including bivalves from localities in the southern coast (Kurian, 1971; Khan et al , 2010; Kundu et al , 2010; Manokaran et al , 2015), east coast (Ansari et al , 1977; Mahapatro et al , 2011), and west coast (Parulekar, 1973; Parulekar & Dwivedi, 1974; Parulekar & Wagh, 1975; Jayaraj et al , 2007). Such studies conducted at a local scale, although common, may be limited in their utility in explaining larger patterns.…”
Section: Discussionmentioning
confidence: 98%
“…; Manokaran et al . ) of the offshore continental shelf of the Bay of Bengal (Parangipettai waters). By contrast, little information is available on the distribution, species‐level composition and diversity of free‐living marine nematodes in this region (Ansari et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the sedimentology (Ajmal Lyla et al 2012;Manokaran et al 2014) and macrobenthic communities (Ajmal Kundu et al 2010;Manokaran et al 2013) of the offshore continental shelf of the Bay of Bengal (Parangipettai waters). By contrast, little information is available on the distribution, species-level composition and diversity of free-living marine nematodes in this region (Ansari et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…(2010) observed the polychaetes to constitute 45% of the total macrobenthic abundance. Manokaran et al (2015) reported that the benthic fauna consisted mainly of polychaetes (88.51%) in all three depth zones (shallow (30–75 m), middle (76–150 m) and deeper (>150 m)) of the south-east continental shelf. Joydas & Damodaran (2009) also observed the dominance of polychaetes (56.97%) in the macrofauna of the shelf in the west coast of India.…”
Section: Discussionmentioning
confidence: 99%